Effect of Silver willow “Russian olive” (Elaeagnus angustifolia) on extensive sheep management - Varga, Krisztina; Csízi, István (Acta Agraria Debreceniensis, 2023)
We carried out a study in the Karcag Research Institute, which affected the areas of narrow-leaved silver willow. In the framework of this research, we performed Balázs’s coenology, and thus established the degree of Borhidi degradation, which resulted in the fact that the areas of the silver willow were degraded practically irreversibly, the diversity of the grassland has decreased. We consider it very important to study these grassland areas of silver willows, as they can provide an additional fodder base for sheep grazing, which will also increase the sustainability of the grassland. The obtained soil analysis results show that the soil samples of the silver willow areas are richer in nitrogen (p-value: 0.006) and phosphorus (p-value: 0.003) than the examined control area.